The validity of evidence derived from invalid procedures (A foundational study) - Aljohani, Badr Fahd Hndi (Journal of Economic, Administrative and Legal Sciences, 2024)
If the hand of justice is not dominant in protecting the rights of individuals to obtain evidence of conviction, we will face criminal chaos, finding loopholes to escape justice. In contrast, the inspectors may violate procedural rules under the guise of the law, claiming the invalidity of evidence obtained from the inspection process. The interest of society and the principles of justice require caution, diligence, and adherence to texts to ensure the legitimacy of the procedure derived from valid evidence. This research aims to understand the concept of evidence derived from invalid procedures, the concept of invalidity, and how Islamic law, the Saudi system, and international conventions address it. It also aims to identify the types and forms of invalidity arising from violations of procedural rules and to understand the use of modern methods to obtain evidence that constitutes an infringement on privacy. The researcher reached several conclusions, including the principle that the invalidity of evidence derived from an invalid procedure in the Saudi system violates Islamic principles, and the practical principle that the invalidity of evidence derived from an invalid procedure does not achieve the purpose of the text and the severity of the defect on the evidence derived from the invalid procedure, and the defect is not the fault of the person involved, whether the accused or others.
Keywords: Validity of Evidence; Invalid Procedures